The Authority of Parents in Marrying Off Their Children: A Normative Analysis of Islamic Law and Its Impact on the Legitimacy of Marriage. - Muhammadong Muhammadong (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The authority of parents in arranging marriages for their children is a significant subject in family law studies, especially from the viewpoint of Islamic law. In Islamic tradition, marriage is regarded as a valid union provided it fulfills specific criteria, including the agreement of the guardian, which in this instance refers to the parents. However, the practice of parents arranging marriages without the child's consent sometimes incites discussions concerning the validity of such unions. This study seeks to examine the authority of parents in arranging marriages for their children in accordance with Islamic law, as well as the legal ramifications of such activities on the legitimacy of the marriage. The research methodology utilized is a normative approach, examining sources of Islamic law including the Qur’an, Hadith, and scholarly opinions to elucidate the essential principles regarding parental power in marriage. This study also looks at how these laws are used in society and how they affect the legitimacy of marriage. The anticipated outcome of this research is an enhanced comprehension of the constraints of parental authority in arranging marriages for their children and its ramifications on the legitimacy of marriage according to Islamic law. This study aims to enhance the evolution of Islamic family law that is equitable and aligned with Sharia principles.